ARK multi-user - Pereira, Pedro (2012)
This paper presents a monitor-based prototype for the visualisation and interaction of an Augmented Reality (AR) system, which recently developed at CCG and demonstrated during the SIACG2002 conference held in Guimarães, Portugal. ARK – Augmented Reality Kiosk - is a set-up based on the prototypes developed in the European Virtual Showcases project to which direct interaction has been added. A normal monitor and a half-silvered mirror constitute the usual set-up for the kiosk. By integrating a half-silvered mirror and a black virtual hand, the CCG solution solves the occlusion problem that normally occurs when a user interacts with a virtual environment displayed by a monitor or other projection system. Conceived with limited monetary resources this portable solution can be deployed in different application contexts as, for instance, culture heritage. This paper presents an extension of the solution to a multi-user platform for a Portuguese museum.